Mexico and her military chieftains, from the revolution of Hidalgo to the present time : Comprising sketches of the lives of Hidalgo, Morelos, Iturbide, Santa Anna, Gomez, Farias, Bustamente, Paredes, Almonte, Arista, Alaman, Ampudia, Herrera, and De la Vega. by Fay. Robinson. Illustratd by twelve portraits and engravings. - Robinson, Fayette (2015)
UANL